HIGH 143ND/144ND IN EXTREMELY DEPLETED MANTLE ROCKS - Sharma M.; Wasserburg G.J.; Papanastassiou D.A.; Quick J.E.; Sharkov E.V.; Lazko E.E. (My University, 1995)
Using an iron hydroxide precipitation to concentrate the rare earth elements it was possible to obtain precise Nd isotopic data on ultramafic rocks. Four samples of unserpentinized harzburgite from the Voykar ophiolite, Polar Urals, are characterized by extreme depletion in fertile components including light rare earth elements down to ∼ 1.7 ppb Nd. These samples have fSm/Nd values > +1 and εNd(O) values ranging from +21 to +47, the highest ever measured in terrestrial whole rock samples. Combined εNd and εSr values of the ultramafic and mafic rocks and a leach indicate that alteration from seawater and/or groundwater is orders of magnitude less than required to produce a detectable change in the εNd values even in samples with > 50% serpentine. Three of the harzburgites plot on a Sm-Nd whole rock array along with samples of dunite, websterite, gabbro and diabase from the ophiolite. The slope of the array corresponds to an age of 387 ± 34 Ma and an initial εNd = +8.6 ± 1.8. These results indicate that the oceanic crustal rocks and the harzburgites are complementary and come from a MORB source. While the linear 147Sm/144Nd-143Nd/144Nd correlation is consistent with this model, one sample of harzburgite is far removed from the array, indicating the presence of older, depleted mantle material that is unrelated to the crustal section. This must be locally available in the upper mantle for tectonic occlusion during obduction of the ophiolite. Alternatively, this “aberrant” sample may represent the original ultrabasic section from older basalt extraction that was permeated by basalts derived from much deeper layers that provided the Voykar ophiolite crust. The major-element and low-REE-compositions of the Voykar harzburgites can be formed by progressive extraction of melt from an undepleted mantle protolith with the requirement that melt separation began in the garnet lherzolite stability field. The extreme chemical and isotopic characteristics of the Voykar harzburgites demonstrate that extraction of partial melt can generate an upper mantle with highly variable εNd and very low Nd concentrations. The potential presence of large amounts of such material in the upper mantle poses an intriguing geochemical problem in that its bulk isotopic signature may not be detectably expressed in basalts, which are dominated by sources with higher average Nd concentrations and much lower εNd and fSm/Nd.